Indefinite intertwining operators - Baldoni-Silva, M. W. (1984)
For a wide class of linear connected semisimple Lie groups, one obtains formulas limiting the Langlands parameters of irreducible unitary representations obtained from maximal parabolic subgroups. The formulas relate unitarity to the number of roots satisfying certain conditions. Some evidence is presented that the formulas are sharp. The results confirm aspects of conjectures that relate unitary parameters to cohomological induction.